Postmastectomy Radiation Therapy: An Overview for the Practicing Surgeon. (11th September 2013) - Jagsi, Reshma
Abstract : Locoregional control of breast cancer is the shared domain and responsibility of surgeons and radiation oncologists. Because surgeons are often the first providers to discuss locoregional control and recurrence risks with patients and because they serve in a key gatekeeping role as referring providers for radiation therapy, a sophisticated understanding of the evidence regarding radiotherapy in breast cancer management is essential for the practicing surgeon. This paper synthesizes the complex and evolving evidence regarding the role of radiation therapy after mastectomy. Although substantial evidence indicates that radiation therapy can reduce the risk of locoregional failure after mastectomy (with a relative reduction of risk of approximately two-thirds), debate persists regarding the specific subgroups who have sufficient risks of residual microscopic locoregional disease after mastectomy to warrant treatment with radiation. This paper reviews the evidence available to guide appropriate referral and patient decision making, with special attention to areas of controversy, including patients with limited nodal disease, those with large tumors but negative nodes, node-negative patients with high risk features, patients who have received systemic chemotherapy in the neoadjuvant setting, and patients who may wish to integrate radiation therapy with breast reconstruction surgery.